ChemInform Abstract: Steroids and Ceramide from the Stem Bark of Odyendyea gabonensis. Issue 50 (10th December 2013) - Happi, Emmanuel Ngeufa; Fannang, Simone Veronique; Fomani, Marie; Donkwe, Suzy Mireille Moladje; Nicaise, Nkoungou Yomzak Carine; Wansi, Jean Duplex; Sewald, Norbert
Abstract Two new steroids (I) and (II) and one new ceramide (III) are isolated from the methylene chloride extract of the stem bark of Odyendyea gabonensis together with 11 known compounds.